Florophytocenotic Diversity of the Western Caucasus - S. A. Litvinskaya (Юг России: экология, развитие)
Aim. To identify the modern phytocenotic and floristic diversity of the Western Caucasus and to present the specifics of its florocenocomplexes.Material and Methods. The article is written on the basis of many years of expeditionary and stationary research using classical geobotanical methods.Results. According to research the flora of the region comprises about 3,500 species of vascular plants from 178 families and 936 genera, indicating a high level of floristic diversity. The spectrum of the leading families of the Western Caucasus is close to the Mediterranean type. The region’s flora has a high index of endemism. The vegetation cover is characterized by latitudinal and altitudinal zonation. The sozological significance of ceno‐complexes is shown. The principal vegetation types of the region are considered: the ancient flood‐littoral landscapes of the river Kuban delta, the psammophilic littoral vegetation with specific rare species of the Azov Sea and the Black Sea, steppe communities, mountain forests, ecotone zone of crooked and subalpine forests, subalpine and alpine meadows and carpets. A petrophytic flora complex (Petrophyton) is represented in each altitudinal zone. For high mountain petrophytic cenoses, the cenotic structure and endemic species are given. The floristic and cenotic differentiation of the forests of the Western Caucasus is conidered.Conclusions.The Western Caucasus is one of the centres of floristic and cenotic diversity of the Caucasian ecoregion. It is characterized by a high population and species diversity, a large number of endemic species and ceno‐complexes. The Western Caucasus is a refugium of ancient ecosystems with Colchidic and Mediterranean roots.